Laryngeal dysfunction is prominent in asthmatic women treated by inhaled corticosteroids. Issue 12 (9th December 2022) - Migueres, Nicolas; Delmas, Christina; Petit Thomas, Julie; Kuntz, Hélène; Peri‐Fontaa, Elisabeth; Schultz, Philippe; Velten, Michel; de Blay, Frédéric
Abstract: Background: Dysphonia is a frequent comorbidity of asthma and has been suggested to be a local side effect of inhaled corticosteroids due to laryngeal candidiasis. We hypothesized that dysphonia in asthmatics was not due to laryngeal organic lesions but to laryngeal dysfunction during phonation (LDP). Objective: We compared the frequency of LDP in female asthmatic patients treated with inhaled corticosteroids to female controls. Methods: We compared 68 asthmatic female patients to 53 female control subjects. Pulmonary function tests were performed and the asthmatic patients classified according to the level of inhaled corticosteroids. Dysphonia was defined as a Vocal Handicap Index ≥18 or GRBAS score ≥2. All patients underwent video laryngo‐strobe examination, analyzed blindly and separately by two otolaryngologists, describing mucosal changes, LDP, or Organic lesions linked to Laryngeal Dysfunction during Phonation (OLDP). Results: 66.2% of the asthmatic patients exhibited dysphonia and 11.3% of controls ( p  < 0.001). No laryngeal candidiasis was found, only 3 patients presented laryngeal mucosa inflammation. LDP was observed in 60.3% of asthmatic patients and 18.9% of controls ( p  < 0.001), and no difference was found for OLDP (11.8% vs. 13.2%). No association was made between LDP, the dosage of inhaled corticosteroid, and bronchial obstruction. Conclusions: Asthmatic patients were more dysphonic than control subjects. This phenomenon was not explained by mucosal inflammation, laryngeal candidiasis or OLDP. Asthmatic patients had more LDP than controls. There was no relation between LDP, inhaled corticosteroids dosage or bronchial obstruction. These results change our view of inhaled corticosteroid side effects in female asthmatic patients.